Vergifnis ter wille van JHWH se Naam (Ps 25:11) - O’Kennedy, D. F. (HTS teologiese studies, 2008)
Forgiveness for the sake of YHWH’s Name (Ps 25:11) This article investigates the concept of divine forgiveness as illustrated in Psalm 25, especially verse 11. Psalm 25:11 is one of only four references in the Psalms where the Hebrew stem (forgive is found). Scholars agree that the petition for forgiveness in verse 11 forms the core or centre of the entire Psalm. This article will offer a possible answer to the following question: what motivates the supplicant to ask for forgiveness? In contrast to other forgiveness passages the Psalmist does not regard repentance or obedience as motivation for the petition. He rather emphasizes the fact that his sin is great (v 11b). The true motivation for this prayer for forgiveness lies in the Name and honor of YHWH (v 11a). He experienced YHWH as ’n faithful God in the past; therefore he has the courage and honesty to plea for forgiveness.